(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2025)
The article highlights the importance of creating social media content in the modern media scape, along with relevant experiences and challenges. It emphasizes the need to consider several key factors in producing social content, due to the necessity of information objectivity and concise analytical formats in today’s media space. The article outlines the findings based on analysis in this field.